Dengue Hemorrhagic Fever (Dhf) Prevention Behavior Among Housewives In The Catchment Area Of Sawah Lebar Community Health Center, Bengkulu City - Didan Yehezkiel Bima Putra; rini patroni; dino sumaryono; reny suryanti (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2026)
Dengue hemorrhagic fever is a public health problem in tropical and sub-tropical regions of the world. Over the last fifty years the disease, caused by a virus from mosquito bites, has spread with a thirty-fold increase in global incidence. Indonesian people still do not realize the importance of maintaining a clean environment. One of the common problems found is a lack of awareness of maintaining the cleanliness of water containers in the environment where they live. This study aims to find out how dengue hemorrhagic fever (DBD) prevention behavior occurs among housewives in the working area of the Sawah Lebar Community Health Center, Bengkulu City. This research is a qualitative research. The results are presented in the form of descriptive data which is arranged using words according to the results of observations, FGDs and in-depth interviews with informants. There were twenty two informants in this study, namely, twenty main informants who were housewives and two supporting informants. The results of this study show that the informants have implemented dengue hemorrhagic fever prevention behavior with 3M Plus, there are still obstacles in using abate powder which is not available, which makes the mother's behavior lacking in preventing dengue hemorrhagic fever (DHF). It is recommended that the Sawah Lebar Community Health Center evaluate the implementation of 3M Plus so that mothers can carry out optimal dengue fever prevention behavior.